Questions pupils ask - Foster, Colin (Mathematical Association, 2017)
If two minuses make a plus, why don’t two pluses make a minus? Is there a formula for factorial? And why isn’t pi a whole number? In this collection of over 40 articles from the journals Mathematics in School and Symmetry Plus, Colin Foster takes Questions Pupils Ask about mathematics as his starting point for a series of reflections on learning and teaching secondary mathematics.